Factors Associated with the Inappropriate Use of Antimicrobials. (2nd December 2014) - McIntosh, W.; Dean, W.
Summary: Antimicrobial resistance continues to grow and antimicrobial use in food animal production and to a lesser extent in human patients is under fire. Much of the criticism has to do with the misapplication of these drugs in both settings. Research indicates that patients, food animal producers, physicians and veterinarians have all played a part in misusing antimicrobials, often because of mistaken beliefs. This paper reviews this research and introduces a theoretical perspective, the Theory of Planned Behavior (TPB), which broadens our understanding of the motivations for misuse. In particular this approach shows that individuals making decisions about antimicrobial use take into account social pressures from and a sense of obligation to significant others in their social networks. Our own work summarized in this paper indicates that both feedlot veterinarians and feedlot managers' antimicrobial decisions are influenced by both expectations from and obligations to a variety of actors in the feedlot network (other veterinarians, feedlot clients, consumers, pharmaceutical companies, and regulatory bodies). Generally across 4 circumstances of antimicrobial use (for acutely sick cattle, chronically‐sick cattle, at‐risk cattle, high‐risk cattle), it is largely the perception that peers and clients expect feedlot veterinarians to use antimicrobials and feedlot veterinarians sense of obligation to these groups that have the most influence on their decisions to recommend antimicrobials. Based on these findings, the question of engaging in changing the choices made by those working with food animals must start with those who influence the decision to proscribe or use antimicrobials. As our data come from the United States and may be unique relative to other countries, these efforts should begin by ascertaining who influences these decisions. The next step is to then change the beliefs of these significant others.